Advancing the understanding of coastal disturbances with a network‐of‐networks approach - Allison N. Myers‐Pigg; Diana Moanga; Ben Bond‐Lamberty; Nicholas D. Ward; J. Patrick Megonigal; Elliott White Jr; Vanessa L. Bailey; Matthew L. Kirwan (Ecosphere)
Abstract Coastal ecosystems are at the nexus of many high priority challenges in environmental sciences, including predicting the influences of compounding disturbances exacerbated by climate change on biogeochemical cycling. While research in coastal science is fundamentally transdisciplinary—as drivers of biogeochemical and ecological processes often span scientific and environmental domains—traditional place–based approaches are still often employed to understand coastal ecosystems. We argue that a macrosystems science perspective, including the integration across distributed research sites, is crucial to understand how compounding disturbances affect coastal ecosystems. We suggest that many grand challenge questions, such as advancing continental‐scale process understanding of extreme events and global change, will only be addressed in coastal ecosystems using a network‐of‐networks approach. We identify specific ways that existing research efforts can maximize benefit across multiple interested parties, and where additional infrastructure investments might increase return‐on‐investment along the coast, using the coastal continental United States as a case study.